Kajian Teknis Optimasi Produksi Alat Gali-Muat dan Angkut pada Overburden Removal - Fakhri Akbar Dzulfikar; Zaenal; Elfida Moralista (Jurnal Riset Teknik Pertambangan, 2023)
Abstract. PT Pancaran Surya Abadi is a coal mining company located in Muara Badak District, Kutai Kartanegara Regency, East Kalimantan Province, employing the surface mining system. Based on the company's productivity data in February 2023, the actual overburden excavation in Pit B1 East Block reached 80,946.00 BCM, accounting for 33.15% of the planned production target of 244,160.00 BCM. The discrepancy led to obstacles in coal production due to a mismatch between digging-loading and hauling equipment (match factor) and road geometry not meeting applicable standards. Consequently, this study evaluates the production shortfall by assessing the technical fleet determination to optimize the overburden removal process. The technical evaluation involves simulating the match factor and adjusting related variables to determine the optimal number of machines in the fleet. The analysis refers to Ministerial Decree ESDM 1827/2018 and AASHTO (American Association of State Highway and Transportation Officials) 1965 for technical road geometry recommendations supporting optimal fleet productivity. Field research in February-March 2023 yielded a match factor of 0.85 and a production rate of 164.03 BCM/hour, achieving 75.24% of the hourly production target. Optimization increased the match factor to 1.03, raising production to 230.91 BCM/hour or 258,622.18 BCM/month, ensuring the attainment of the 218 BCM/hour productive day shift target. Abstrak. PT Pancaran Surya Abadi merupakan perusahaan pertambangan batubara yang berlokasi di Kecamatan Muara Badak, Kabupaten Kutai Kartanegara, Provinsi Kalimantan Timur, dan menggunakan sistem penambangan terbuka. Berdasarkan data produktivitas perusahaan pada bulan Februari 2023, penggalian overburden aktual di Pit B1 Blok Timur mencapai 80.946,00 BCM, yang merupakan 33,15% dari target produksi rencana sebesar 244.160,00 BCM. Ketidaksesuaian ini menyebabkan hambatan dalam produksi batubara karena ketidakcocokan antara peralatan penggalian-pemuatan dan pengangkutan (match factor) serta geometri jalan yang tidak memenuhi standar yang berlaku. Oleh karena itu, penelitian ini mengevaluasi ketidakcapaian produksi dengan menilai penentuan armada teknis untuk mengoptimalkan proses pengangkatan overburden. Evaluasi teknis melibatkan simulasi match factor dan penyesuaian variabel terkait untuk menentukan jumlah optimal mesin dalam armada. Analisis mengacu pada Keputusan Menteri ESDM 1827/2018 dan AASHTO (American Association of State Highway and Transportation Officials) 1965 untuk rekomendasi geometri jalan teknis yang mendukung produktivitas armada yang optimal. Penelitian lapangan pada Februari-Maret 2023 menghasilkan match factor sebesar 0,85 dan produksi sebesar 164,03 BCM/jam, mencapai 75,24% dari target produksi per jam. Optimasi meningkatkan match factor menjadi 1,03, meningkatkan produksi menjadi 230,91 BCM/jam atau 258.622,18 BCM/bulan, memastikan pencapaian target produksi per jam pada shift kerja yang produktif sebesar 218 BCM/jam.